The nursing psychiatric teaching new forms meaning: nursing students perception in the stage field - Maria Salete Bessa Jorge; Norma Faustino Rocha (Rev Rene)
The work reports the nursing students perception in the stage field of a nursing psiquiatric discipline. It began some decades ago with the configuration of the Brazilian Movement of Psiquiatric Reform whose primordial goal consisted on questioning and contandingthe traditional role of psyquiatric institutions and psiquiatry as scientific knowledge. To investigate the meaning of stage’s experience in the Psyquiatric Nursing’s discipline, we interviewed 15 students which were undertaking a curricular stage in a Mental Health’s field. The instrument used was an interview which objectifies the obtainment of informations related to the theme. The data’s interpretation was done based on the interviewers speeches, the selected method was the content analyse according to a construction of categories. The results achieved revealed possibilities of changes in the students’ “self” as well as in their relations with mental disorders’ patients.